Pengaruh Pendekatan Realistic Mathematics Education Terhadap Kemampuan Representasi Matematis Siswa di Kelas VIII SMPN 1 Banuhampu - Chairul Fajri; Rusdi; Nola Nari; Gema Hista Medika (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of the Realistic Mathematics Education approach on the mathematical representation ability of eighth-grade students at SMPN 1 Banuhampu. The study used a pre-experimental method with a Static Group Comparison Design. The study population was all eighth-grade students consisting of nine classes. The sample was selected through a random sampling technique after conducting normality tests, homogeneity of variance, and equality of means, resulting in class VIII.7 as the experimental class and class VIII.9 as the control class. The experimental class was given learning using the Realistic Mathematics Education approach, while the control class used conventional learning. The research instrument was a mathematical representation ability test given after the treatment. Data were analyzed using the t-test after fulfilling the prerequisite tests for normality and homogeneity. The results showed that the average mathematical representation ability of students in the experimental class was higher than the control class. The results of the t-test and the P-value obtained showed that the difference was statistically significant. Thus, it can be concluded that the Realistic Mathematics Education approach has a significant effect on improving the mathematical representation ability of eighth-grade students at SMPN 1 Banuhampu